Relationship between locomotion and communication incapacities and scholarship in patients with cerebral palsy - Rodriguez Ramirez, María (2023)
Objective: to evaluate the relationship between severity of locomotion and communication incapacities and scholarship in patients with brain palsy. Methods: cross-sectional study carried out in 316 patients from 3-12 years of age with cerebral palsy attended from July 2016 and June 2017 at the Instituto Nacional de Rehabilitación "Dra. Adriana Rebaza Flores" AMISTAD PERU-JAPÓN, Lima-Peru. Results: mean age was 6 years (range 3-12); 57% were males. Spastic cerebral palsy was found in 69.7% followed by dyskinetic cerebral palsy in 20%; 69.6% were in the school and more than 50% of them had severe locomotion and communications incapacities. An inverse relationship was found between severity of locomotion and communications incapacities and scholarship. Conclusions: Children with cerebral palsy who have locomotion and communications incapacities tended to have less school attendance.